Music Training in the Ekaterinburg Diocesan Women’s School at the Turn of the 19th–20th Centuries in the Context of Religious and Musical Education of the Region - Oksana E. Sheludyakova (Вестник Екатеринбургской духовной семинарии, 2022)
The article is devoted to studying the traditions of Church singing education in the Urals on the example of Ekaterinburg Diocesan Women’s School. The author aims to reconstruct the main activities of the school on the basis of archive materials, to identify the role of subject «Church Singing» in teaching and upbringing and to consider some methodological aspects of teaching. The article provides a brief summary of teaching and learning process, the activities reflecting the skills formed during Church Singing lessons, and describes the teaching aids used in the process.